Pengaruh Kecanggihan Investor terhadap Ketepatan Reaksi Pasar dalam Merespon Pengumuman Dividen Meningkat - Marfuah Marfuah (Jurnal Akuntansi dan Auditing Indonesia, 2006)
The primary purpose of this study is to test the impact of investor sophistication toward the accuracy of market reactions in responding dividend increase announcement at the Jakarta Stock Exchange. The study employs the proportion of firm shares held by institutional investors as the proxy for investor sophistication. The sample for this research is 80 companies during the period of 2000-2002. The result indicates there is no impact of investor sophistication toward accuracy of market reactions in responding dividend increase announcement at Jakarta Stock Exchange.Keyword: dividend increase, information content, decisionally efficient market, investor sophistication, institutional ownership.